Pengaruh Tingkat Inflasi, Tingkat Suku Bunga dan Kurs terhadap Indeks Harga Saham Gabungan pada Sektor Industri Dasar dan Kimia yang Terdaftar di Bursa Efek Indonesia Periode 2015-2017 - Nina Purnasari; Ahyuli Nelsy Manurung; Sri Weninta Br. Sitepu; Theresya Mey Riska Malau; Febri Dwi Putri (Ekonomis: Journal of Economics and Business, 2020)
Research aims to obtain information on whether inflation rates, interest rates and exchange rates on the composite stock price index both simultaneosudly and partially impact on basic industrial and chemical sectors in idx 2015-2017 period. The explanatory examination of the quantitative approach is the type used in this research, because the testing data relies on the quantity and analysis of the data obtained with statistical analysis. As for the use of methods to analyze the results of research, it is linear regression. There were 66 populations of the company in 2015-2017, with a sample number of 41. Independent variables simultaneously affect dependent variables, but interest rates and exchange rates are partial and significant to CSPI, while inflation rates are not significant and affect to CSPI. According to the research, it can be concluded that theresult of the Determination Coefficient on the Adjusted R Square has a value of 9.9%, the inflation rates, interest rates and exchange rates affect CSPI and 90.1% are not included in the variables.